2011
DOI: 10.3892/ijo.2011.1138
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived vascular endothelial growth factor (VEGF)-A facilitates tumor metastasis through the VEGF-VEGFR1 signaling pathway

Abstract: Abstract. Vascular endothelial growth factor (VEGF) and its receptors are involved in carcinogenesis, invasion and tumor angiogenesis, but the underlying mechanism by which VEGF promotes tumor metastasis is poorly understood. In this study, we show that in cancer patients high expression of VEGF is correlated with metastasis, and anti-VEGF treatment (bevacizumab) has clinical effects on tumor metastasis. Two human lung carcinoma cell lines (A549 and SPCA1 cells) with distinct VEGF expression were injected intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…EGFR overexpression is linked to invasion and metastasis of multiple types of cancer (Lu et al, 2001). VEGFA facilitates tumor metastasis (Liu et al, 2011). MMPs enhance cell invasion and metastasis by digesting extracellular matrix (Kessenbrock et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…EGFR overexpression is linked to invasion and metastasis of multiple types of cancer (Lu et al, 2001). VEGFA facilitates tumor metastasis (Liu et al, 2011). MMPs enhance cell invasion and metastasis by digesting extracellular matrix (Kessenbrock et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the increased secretion of SHH and VEGF also indicated the enrichment of PCSC-like cells in 3D matrix. SHH has been associated with PCSCs and drug resistance to chemotherapy [6,10,11], and VEGF is an important marker during carcinogenesis and metastasis [42,43]. One of the potential explanations of the increase of SHH and VEGF expression in 3D hydrogel is hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that in lung cancer patients high expression of VEGF correlates with metastasis. In addition, VEGF secreted by human A549 lung carcinoma cells facilitates tumor metastasis in a murine model [8]. A systematic review of published studies indicates that VEGF overexpression is associated with a poor prognosis in both non-small cell lung cancer (NSCLC) and small cell lung cancers [9].…”
Section: Introductionmentioning
confidence: 99%